2003
DOI: 10.3727/000000003108747352
|View full text |Cite
|
Sign up to set email alerts
|

Improved Efficacy of Stem Cell Labeling for Magnetic Resonance Imaging Studies by the Use of Cationic Liposomes

Abstract: Labeling stem cells with FDA-approved superparamagnetic iron oxide particles makes it possible to track cells in vivo with magnetic resonance imaging (MRI), but high intracellular levels of iron can cause free radical formation and cytotoxicity. We hypothesized that the use of cationic liposomes would increase labeling efficiency without toxic effects. Rabbit skeletal myoblasts were labeled with iron oxide by: 1) uptake of iron oxide incorporated into cationic transfection liposomes (group I) or 2) customary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 22 publications
1
60
1
1
Order By: Relevance
“…In previous studies, we investigated the function of hematopoietic cells more extensively and did not find any impairment of the cells due to our labeling procedure (26,39). This is in accordance with data from the literature (17,20,22,25,(40)(41)(42). The migration properties of our cells were apparently not impaired, otherwise they had not reached the tumor tissue after intravenous administration.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, we investigated the function of hematopoietic cells more extensively and did not find any impairment of the cells due to our labeling procedure (26,39). This is in accordance with data from the literature (17,20,22,25,(40)(41)(42). The migration properties of our cells were apparently not impaired, otherwise they had not reached the tumor tissue after intravenous administration.…”
Section: Discussionsupporting
confidence: 91%
“…14 Here we used Effectene to transfect the MRI contrast agent Gd-DTPA into stem cells, because it is relatively more efficient and less toxic than liposome, calcium phosphate, or viral vectors for transfection into primary cells. [15][16][17] There was a possibility that phagocytosed or dead transplanted cells with Gd-DTPA were detected by the MRI. However, a previous pharmacokinetic study reported that Gd-DTPA in dead cells or interstitial spaces was washed out within 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Other organs including heart, spleen, lung, kidney, and brain showed no sign of pathological changes such as edema, atrophy, steatosis, liquefaction necrosis, hyalinization, calcification, and hemosiderosis compared with the corresponding organs from the dogs in the control group ( Figure 9B-F [26][27][28] On the other hand, some researchers reported that bare Fe 3 O 4 -MNPs induced the formation of free hydroxyl radical species that reacted with intracellular constituents such as the cell's endogenous DNA, thus inhibiting cellular function and proliferation. 29,30 Moreover, it was found that exposure to dextran-or citric acid-coated Fe 3 O 4 -MNPs, of an approximate size of 31-38 nm, resulted in a dose-dependent decrease of HUVEC viability in vitro. 31 These results confirm that the toxicity of Fe 3 O 4 -MNPs affect the biocompatibility and biosafety in vitro.…”
Section: Effect Of Fe 3 O 4 @Au Composite Mnps On the Organsmentioning
confidence: 99%